The Effect of Interest Rates, Inflation, and Rupiah Exchange Rates on the LQ45 Mining Stock Price - Julio Santos Siagian; Harlyn Siagian; Judith Sinaga (Journal of Educational Management Research, 2026)
This research is motivated by the high volatility of the stock market on the Indonesia Stock Exchange which is influenced by macroeconomic variables, such as interest rates, inflation, and rupiah exchange rates, especially in the mining sector which is sensitive to global dynamics. The purpose of this study is to analyze the influence of these variables on the share prices of mining companies that are members of the LQ45 Index for the 2020–2024 period. The method used is a causal quantitative approach with multiple linear regression analysis based on monthly time series data, accompanied by classical assumption tests to ensure the validity of the model. The results of the study show that partially inflation and the rupiah exchange rate have a significant effect on stock prices, while interest rates do not have a significant effect. However, simultaneously these three variables have a significant effect on stock prices. In conclusion, macroeconomic factors have an important role in determining the movement of stock prices in the mining sector. The contribution of this research lies in the integration of macroeconomic analysis with the perspective of strategic financial management in investment decision-making.